The Relationship Between Knowledge Level and Medication Adherence Among Pulmonary Tuberculosis Patients at Arifin Achmad Regional General Hospital, Pekanbaru - Wahyu Margi Sidoretno; Hera Dameira; Sri Kartini (Jurnal Ilmu Kesehatan Abdurrab, 2026)
Pulmonary tuberculosis remains one of the major public health problems in Indonesia, as it requires long-term treatment and optimal patient adherence. Patients’ knowledge regarding the disease, therapeutic regimen, treatment duration, and consequences of non-adherence plays an important role in supporting successful tuberculosis therapy. This study aimed to analyse the association between knowledge level and medication adherence among patients with pulmonary tuberculosis at Arifin Achmad Regional General Hospital, Pekanbaru. This study employed an observational analytic design with a cross-sectional approach. A total of 68 respondents were recruited using a total sampling technique. Data were collected using questionnaires designed to assess patients’ knowledge level and medication adherence. Data analysis was performed using the Spearman Rank correlation test. The results showed a significant positive association between knowledge level and medication adherence among patients with pulmonary tuberculosis, with a p-value of <0.001 and a correlation coefficient of r=0.542. This correlation coefficient indicates a moderate positive relationship, meaning that patients with a higher level of knowledge tend to have better adherence to tuberculosis treatment. This study concludes that knowledge level is significantly associated with medication adherence among patients with pulmonary tuberculosis. Strengthening patient education, medication counseling, and continuous health promotion should be optimized to improve the success of tuberculosis therapy.